Blended learning model during the COVID-19 outbreak: methodological aspects of teaching internal medicine - Vizir, V. A.; Demidenko, O. V.; Sadomov, A. S.; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович; Садомов, Антон Сергійович (My University, 2021)
Blended learning as an important tool of education in modern conditions is directly related to the introduction of new pedagogical methods, which are based on combining traditional approaches to the organization of the educational process and information technology of distance learning. The attractive aspects of such training are the combination of different technologies into a single integrated learning approach. In this case, the presentation of educational materials can take place as part of online lectures or distance learning course, which involves independent work of the student, and in direct discussion, which takes place during classes in real time using distance learning services. This tool is especially important due to the COVID-19 outbreak.
Keywords: тези доповідей